The System of Determining Additional Employee Income (TPP) Based on Paramedics' Performance in Treating Schizophrenic Patients at the Banda Aceh Mental Hospital According to the Ji’ālah Contract - Humaira, Audia; Jamhuri, Jamhuri; Abdullah, Muslem (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
Mental health services require a high level of professionalism, responsibility, and work readiness, particularly in handling patients with severe mental disorders such as schizophrenia. This condition causes paramedics working in mental hospitals to face more complex workloads, the need for intensive supervision, and higher occupational risks compared to general health services. At the Banda Aceh Mental Hospital, civil servant paramedics receive Additional Employee Income (TPP) as a performance-based incentive regulated under Aceh Governor Regulation Number 15 of 2024. This study aims to analyze the mechanism for determining TPP based on the performance of paramedics in treating schizophrenia patients and to examine its conformity with the principles of the ji‘ālah contract in fiqh muamalah. This research employs an empirical legal research method with a normative empirical approach. Primary data were obtained through interviews with the management of the Banda Aceh Mental Hospital who are involved in the performance evaluation process and the management of TPP, while secondary data were collected from Aceh Governor Regulation Number 15 of 2024, governor decrees related to the determination of basic TPP, the fatwa of the National Sharia Council of the Indonesian Ulama Council regarding the ji‘ālah contract, as well as relevant literature on fiqh muamalah. The results show that the determination of TPP for paramedics is based on job class and performance assessment through the e-Kinerja system with a composition of 70% work productivity and 30% work discipline. From the perspective of fiqh muamalah, this mechanism generally reflects the principles of the ji‘ālah contract because there is a relationship between work performance and the compensation received. However, the risks associated with mental health services have not yet been included as a separate indicator in the TPP assessment system. This study contributes to strengthening the normative legitimacy of performance-based incentive policies from an Islamic legal perspective.